Case report: Guillain-Barre syndrome with pneumococcus – A new association in pediatrics. (2018) - Khatib, Hassan El; Naous, Amal; Ghanem, Soha; Dbaibo, Ghassan; Rajab, Mariam
Abstract: Guillain-Barre Syndrome, an acute flaccid paralysis known to be caused by recent Gastro-intestinal infections mainly campylobacter, and Respiratory infections mainly mycoplasma pneumoniae and influenza. One reported case of severe invasive pneumococcal disease in a 68 year old female, that presented with Austrian's triad of meningitis, pneumonia and endocarditis, and progressed to develop Guillain Barre syndrome, an association never been documented before. We present a case of 13 year old male, presented with hypoactivity and inability to bare his own weight, developed septic shock due to pneumococcus with Acute Respiratory Distress Syndrome, and was found to have neurological findings of Guillain-Barre Syndrome. A new association in pediatric age group, never been reported before.